73 The Use of Topical Anaesthetic in The Banding of Internal Haemorrhoids: A Feasibility Study for A Randomized Control Trial. (12th October 2021) - Sharma, V; Sharma, D; Stearns, A; Hernon, J
Abstract: Aim: Rubber band ligation (RBL) is a procedure commonly performed in colorectal clinics for internal haemorrhoids. 90% of patients experience pain following RBL. We aimed to complete a feasibility randomized control trial assessing the role of topical anaesthetic before RBL of internal haemorrhoids. Method: We performed a prospective, single-centre, single blinded, randomized(1:1) controlled feasibility trial. Patients presenting with symptomatic haemorrhoids suitable for banding were randomized to undergo the procedure with local anaesthetic or without(control). Pain scores and vasovagal symptoms were assessed at 0 minutes, 30minutes, 4 hours, and 72 hours after the procedure. Primary outcome measures were recruitment rate, participant retention rate, patient and surgeon acceptability. Secondary outcome measures were pain scores up to 72 hours, vasovagal episodes, new use of analgesia, and adverse outcomes. Results: 35 patients (18 topical anaesthetic, group A; 17 no anaesthetic gel, group B) were recruited. Mean recruitment rate was 11.7 participants per month. 33(94%) participants remained in the study until completion, with 2 patients lost to telephone follow-up. The treatment was acceptable for 35(97%) eligible patients. 1 patient declined enrolment. The treatment was acceptable to all surgeons (100%). There was a significant difference in median pain scores of -2(95% CI -4.0 to -1.0, p = 0.0006) at the 30-minute time point only. There was no significant difference in vasovagal symptoms(p = 0.10) or new analgesia use(p = 0.85). Conclusions: In conclusion, we have shown that a phase III clinical trial is feasible. We have demonstrated excellent patient recruitment and retention as well as patient and surgeon acceptability.